2015
DOI: 10.1007/s11120-015-0209-7
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem II cycle activity and alternative electron transport in the diatom Phaeodactylum tricornutum under dynamic light conditions and nitrogen limitation

Abstract: Alternative electron sinks are an important regulatory mechanism to dissipate excessively absorbed light energy particularly under fast changing dynamic light conditions. In diatoms, the cyclic electron transport (CET) around Photosystem II (PS II) is an alternative electron transport pathway (AET) that contributes to avoidance of overexcitation under high light illumination. The combination of nitrogen limitation and high-intensity irradiance regularly occurs under natural conditions and is expected to force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…Past bench-top studies employed 3 cm-deep rectangular photobioreactors for culture maintenance, to reduce selfshading effects. These studies observed higher levels of NPQ capability and modeling of photophysiology suggested a high degree of AET in excess light [26,63]. This scenario represents what could occur in shallow, non-turbid natural waters.…”
Section: Comparison With Previous Studies Under Natural Light Regimesmentioning
confidence: 72%
See 2 more Smart Citations
“…Past bench-top studies employed 3 cm-deep rectangular photobioreactors for culture maintenance, to reduce selfshading effects. These studies observed higher levels of NPQ capability and modeling of photophysiology suggested a high degree of AET in excess light [26,63]. This scenario represents what could occur in shallow, non-turbid natural waters.…”
Section: Comparison With Previous Studies Under Natural Light Regimesmentioning
confidence: 72%
“…AET rates were not quantified here. However, modeling of Phaeodactylum photophysiology under a sinusoidal light regime predicted that AET could represent an important proportion of the total electron transport in thylakoids [26,63]. The proportion of electrons consumed by AET, measured as light dependent oxygen consumption, increased with increasing growth irradiance in the centric diatom Thalassiosira pseudonana, suggesting AET can be an important component for maintaining redox balance in excess light [21].…”
Section: Changes In Photosynthetic Parameters In Situ and Ex Situ Ovementioning
confidence: 99%
See 1 more Smart Citation
“…The PSII as the heart of the photosynthetic process is highly sensitive to the environmental stresses. Its activity could be determined with one non-invasive time-resolved fluorescence measurement, which could measure the polyphasic rise with the basic steps of OJIP [43,[48][49][50][51][52][53][54]. Several studies have shown that the chlorophyll a transient has become one of the most popular tools to estimate stress-induced changes in photosynthetic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid changes in light climate in well mixed waters or on intertidal flats challenge planktonic and benthic diatoms, respectively, to adjust light harvesting to what can be safely used for photosynthesis. As periods of high light conditions can result in oxidative damage to, in particular, the photosystem II (PSII) core, diatoms possess various mechanisms to deal with high light stress: (1) avoid excess light energy absorption by decreasing cell pigment content (MacIntyre et al ), (2) dissipate excess excitation energy as heat in a process called Non‐Photochemical Quenching of chlorophyll a (Chl a ) fluorescence (NPQ) (Lavaud and Goss ; Goss and Lepetit ), and/or by engaging alternative electron cycling pathways (Wagner et al ), (3) scavenge reactive oxygen species (ROS) (Janknegt et al , 2009 a , b ; Waring et al ), (4) repair damaged PSII cores, mainly by replacing the D1 protein of the PSII reaction center (Wu et al ; Lavaud et al ), (5) behavioral down regulation through vertical cell movement (microcycling and bulk migration) (Kromkamp et al ; Serôdio ). Of the above mechanisms, especially NPQ is able to track fast light fluctuations experienced in the natural habitat (Brunet and Lavaud ; Lavaud and Goss ).…”
mentioning
confidence: 99%